A Case Report of Xp21 Contiguous Gene Syndrome: Adrenal Hypoplasia Congenita, Glycerol Kinase Deficiency, and Duchenne Muscular Dystrophy - Kara, Cengiz; Yilmaz, Gulay Can; Bitkin, Eda Celebi; Aydin, Murat (Journal of clinical research in pediatric endocrinology, 2016)
Objective: X-linked adrenal hypoplasia congenita (AHC) is characterized by primary adrenal insufficiency caused by deletion or mutation of the DAX-1 gene and is frequently associated with hypogonadotropic hypogonadism. It can occur as a part of Xp21 contiguous gene syndrome together with glycerol kinase deficiency and Duchenne muscular dystrophy. We report a new subject with this rare disease. Case: Twin male sibs at the ages of 30 days were hospitalized because of feeding difficulties, vomiting, and weight loss. Parents had no consanguinity and there was no family history of endocrine or renal diseases. One of the twins died in a few hours. Other patient's physical examination revealed that weight was 2100 g (his twin's was 1800 g) and body length 49 cm; blood pressure: 70/40 mm-Hg, heart rate: 140 beats/minute, respiratory rate: 50 breaths/minute, body temperature: 36 [degrees]C. He was dehydrated and lethargic. External genitalia were well developed with intrascrotal testes of 2 mL in volume. There was no skin hyperpigmentation. Laboratory findings were as follows: Na 97 mEq/L, K 5.1 mEq/L, adrenocorticotropic hormone (ACTH) >1250 pg/mL, cortisol 6 [micro]g/dL (3-23), plasma renin activity: 50 ng/mL/hr (3-35), 17(OH)P 18 ng/mL (0.3-1.1), dehydroepiandrosterone sulfate: 24 [micro]g/dL (5-111), luteinizing hormone: 0.71 mU/L (0,02-7), follicle stimulating hormone: 0.43 mU/L (0.16-4.1), total testosterone 0.76 ng/mL (0.7-4). After initial therapy for adrenal crisis, hydrocortisone and fludrocortisone were given at replacement doses. Ten days later, steroid hormone treatment was halted and ACTH stimulation test (250 [micro]g) was performed. Peak levels of cortisol, 17(OH)P, and 11-deoxycortisol were 1.02 [micro]g/dL, 3.11 ng/mL, and 3.2 ng/mL, respectively. This test excluded defects in steroid biosynthesis associated with salt-losing congenital adrenal hyperplasia. On ultrasound examination, adrenal gland could not been visualized. Therefore, a diagnosis of AHC was established. Furthermore, we investigated for contiguous gene syndrome. Serum creatinine phosphokinase [CPK, 9974 U/L, (N:35-195)] and triglyceride [TG, 439 mg/dL, (N:0-200)] levels were markedly elevated. On follow-up period of 9 months, his motor and mental development were noted to be delayed. Array comparative genomic hybridization analysis was planned to show Xp21 deletion syndrome. Conclusion: Serum CPK and TG levels should be measured in all male patients who present with an adrenal hypoplasia. These simple tests may help early diagnosis and appropriate genetic counseling for next pregnancy.